“OKAY BOOMER, LET ME COOK”: LINGUISTIC PERFORMANCE AND GENERATIONAL POWER DYNAMICS IN THE HYUNDAI X AMAZON ‘SLANG’ CAMPAIGN - Manjaya, Sofia Imanina E (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2026)
This paper examines how corporate marketing strategies create intergenerational conflict, negotiate authentic status and recreate power through their use of vernacular of youth in their advertisement for the 2025 HyundaiXAmazon “Slang” through CDA. Strategic cringe usage and performative linguistic incompetence in the commercial, demonstrates how the advertisement is a sophisticated meta-narrative and not a failure of strategy; the clumsy use of sophisticated, condensed lexicon (ie. “bussin,” “sus,” and “mid”) representative of GenZ and/or rooted in Black and queer digital communities, reconnects to “stylistic hedging” regarding the promotion and usage of youth vernacular by the brand. The father figure serves to deconstruct traditional authority by representing daughters with substantial linguistic capital, while also allowing the “paternal” figure to regain power through the consumer route. The advertisement provides a pathway for brands to reclaim power as corporations through this foundation of financial exchange, while simultaneously adhering to contemporary standards of cultural awareness. This study concludes that this pattern perpetually accelerates and causes semantic bleaching and commodification of subculture language, positioning neoliberalism as the solution to social and cultural issues complexity. This advertisement further reflects how neoliberal conceptualizations of linguistic identity serve as friction points that can be effectively resolved through platform capitalism.